Sistem Informasi Sumber Daya Manusia (SDM) pada AMIK Luwuk Banggai Berbasis Web - A. Mokodol, Chesya; Tida, Gustavina; Gani, Rosniati; M. Dg. Pasau, Nusmiswari; Ibrahim, Rendi; Putra Yasa, I Ketut; Putu Rika Permana , I Gusti (Pusat Riset dan Inovasi Nasional, 2025)
Human resources (HR) are a vital asset in educational institutions, supporting the continuity of administrative, academic, and service processes. At AMIK Luwuk Banggai, employee data management, attendance tracking, and performance evaluation are still carried out manually using conventional documents, often leading to issues such as data duplication, delayed information, and recording errors. These conditions reduce administrative efficiency and slow down strategic decision-making processes. This study aims to design and develop a web-based human resource information system that can digitally integrate employee data, facilitate attendance recording, and generate real-time performance reports. The development method applied is the Waterfall model, which includes stages of requirement analysis, system design, implementation, testing, and maintenance. Research data were collected through interviews, direct observation, and documentation of administrative processes. The resulting system provides a simple and responsive interface accessible via computers and mobile devices. Testing results indicate that the system improves data accuracy, accelerates report generation, and minimizes administrative errors. Furthermore, the system implementation supports faster and more precise data-driven managerial decision-making. Therefore, this research makes a significant contribution to improving HR management efficiency in vocational higher education and has the potential to serve as a reference for developing similar systems in other educational institutions.